Professional Development Program Aimed at Physicians to Develop Drug Utilization Studies - Yacelis Dahilet Cisneros Nápoles; Pedro Milián Vázquez; Maira Quiroz Enríquez; Yaikibel Soto Navarro; Moraima Pérez Fonseca; Eidys Rodríguez Herrera (Medisur)
Background: one of the deficiencies presented by physicians in their professional activity is related to the development of drug utilization studies. Objective: to design a professional development program aimed at physicians to develop drug utilization studies. Methods: an educational research was conducted at the Faculty of Medical Sciences of Cienfuegos during the 2011-2012 academic year. Theoretical methods such as the analytic-synthetic, the inductive-deductive, the historical-logical, modeling and system approach were used in the methodological and theoretical process. Results: the program aims at training physicians to develop drug utilization studies and its contents include: drug-related problems; criteria for selecting a drug in the prescription process; Pharmacoepidemiology; objectives, types of studies, characteristics and steps for the design and development of drug utilization studies; drug therapy and aspects on the selection and analysis of drug information sources. The methods are based on reflection and research itself developed by physicians during the activities for their professional development. Discussion and presentation of essays and research projects will be used to assess learning in the program, which integrates forms of professional development including specialized conferences, self-study, postgraduate courses, workshops and consultancies. Conclusions: the program serves as a reference to design the different activities required to train physicians for the development of drug utilization studies and it can be integrated in the graduate strategy of the university.